2009
DOI: 10.1007/s11739-009-0323-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of evidence: the Cochrane systematic review of organised stroke care

Abstract: In 2007, the first commentary hosted by this Cochrane's Corner focussed on stroke units and discussed the principle that a valid combination of results from a series of unbiased primary studies can provide influential information that would not be otherwise available by individual studies [1]. We now present a case study of the role played by the stroke unit Cochrane review in the complicated process that led to changes in clinical practice and health policy. Our hypothesis is that the theoretical and pragmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for systematic reviews were followed (11,12).…”
mentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement for systematic reviews were followed (11,12).…”
mentioning
confidence: 99%
“…It has been shown that more organized stroke care improves patients’ outcome and in Finland, Meretoja et al have found in an extensive register‐based study, an association between the level of acute stroke care and the case fatality. The development of acute care in the 1990s first occurred in university hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This bibliographic search was conducted following PRISMA (Preferred Reporting Items for Systemic Reviews and Meta-Analyses, http://www.prisma-statement.org) guidelines for systematic reviews and meta-analyses (PROSPERO registration number: CRD42020192264). The review also fulfilled the PRISMA 2009 Checklist [11]. The PICO (population, intervention, comparison, and outcome) question was, 'Which is efficacy of computer-aided static navigation techniques on the accuracy of endodontic microsurgery?'…”
Section: Methodsmentioning
confidence: 99%